2019
DOI: 10.1038/s41598-019-40150-3
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Central Pacific reefs subject to frequent heat stress and human disturbance

Abstract: Frequent occurrences of coral bleaching and associated coral mortality over recent decades have raised concerns about the survival of coral reefs in a warming planet. The El Niño-influenced coral reefs in the central Gilbert Islands of the Republic of Kiribati, which experience years with prolonged heat stress more frequently than 99% of the world’s reefs, may serve as a natural model for coral community response to frequent heat stress. Here we use nine years of survey data (2004–2012) and a suite of remote s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 46 publications
4
52
0
1
Order By: Relevance
“…Differential rates and clearly identified causes of mortality and recovery among taxa create challenges for large‐scale evaluations of climate impacts (Darling et al, 2019; McClanahan et al, 2001). Estimating mortality requires inter‐annual monitoring to evaluate changes that could be poorly tied to heat stress alone (Darling et al, 2013; Donner & Carilli, 2019). While we acknowledge this weakness, bleaching is currently the most commonly used and quantifiable way to measure sensitivity to heat stress (Donner et al, 2017; Sully et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential rates and clearly identified causes of mortality and recovery among taxa create challenges for large‐scale evaluations of climate impacts (Darling et al, 2019; McClanahan et al, 2001). Estimating mortality requires inter‐annual monitoring to evaluate changes that could be poorly tied to heat stress alone (Darling et al, 2013; Donner & Carilli, 2019). While we acknowledge this weakness, bleaching is currently the most commonly used and quantifiable way to measure sensitivity to heat stress (Donner et al, 2017; Sully et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The CTA model is based on the concept of cumulative degree‐heating weeks or months, or the amount of excess temperatures above a summer baseline, and is the most commonly used metric to assess the probability of coral bleaching and the future state of coral reefs (Donner & Carilli, 2019; Eakin et al, 2010; Van Hooidonk et al, 2013). To estimate CTAs, we extracted daily SST time series for each site from the 5‐km NOAA Coral Reef Watch version 3.1 products between 1985 and 2015, available from the NOAA website (https://coralreefwatch.noaa.gov/product/5km/).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a modeling study projecting future coral bleaching (Logan, Dunne, Eakin, & Donner, ) found that calculations based on the previous 60 years (a rolling window that approximates genetic adaptation) decreased predicted bleaching frequencies by up to 80% when compared to calculations based on a static window. Furthermore, there is evidence that temperature variability is beneficial to coral TST: past exposure to a greater range of temperatures may lead to increased thermotolerance in some coral species (Bay & Palumbi, ; Carilli, Donner, & Hartmann, ; Mayfield, Chan, Putnam, Chen, & Fan, ; Putnam, Barott, Ainsworth, & Gates, ; Rivest, Comeau, & Cornwall, ) and coral communities as a whole (Ainsworth et al, ; Donner, ; Donner & Carilli, ; Guest et al, ; Hughes et al, ; McClanahan & Maina, ; Sully, Burkepile, Donovan, Hodgson, & Woesik, ; Thompson & van Woesik, ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that there is higher vulnerability to regional-scale disturbance at locations that rely heavily on external recruitment. coral communities as a whole (Ainsworth et al, 2016;Donner, 2011;Donner & Carilli, 2019;Guest et al, 2012;Hughes et al, 2019;McClanahan & Maina, 2003;Sully, Burkepile, Donovan, Hodgson, & Woesik, 2019;Thompson & van Woesik, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We considered two exposure models, one based on a single variable of excess temperature exposure (cumulative degree heating weeks, the CTA model) and one based on a multivariate environmental index of climate exposure (CE) that integrates temperature, winds and water flow into a weighted metric of exposure. The CTA model is based on the concept of cumulative degree heating weeks or months, or the amount of excess temperatures above a summer baseline, and is the most commonly used metric to assess the probability of coral bleaching and the future state of coral reefs (Eakin et al 2010;van Hooidonk et al 2013;Donner & Carilli 2019). For each site, we extracted daily SST time series from the 5-km NOAA Coral Reef Watch version 3.1 products between 1985 and 2015, available from the NOAA website (https://coralreefwatch.noaa.gov/satellite/bleaching5km/index.php).…”
Section: Exposurementioning
confidence: 99%